2020
DOI: 10.1002/bjs.11613
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer diagnosis based on lipid profiling by probe electrospray ionization mass spectrometry

Abstract: Probe electrospray ionization mass spectrometry (PESI‐MS) is an ambient ionization‐based mass spectrometry method that surpasses the original electrospray ionization technique in features such as the rapidity of analysis, simplicity of the equipment and procedure, and lower cost. This study found that the PESI‐MS system with machine learning has the potential to establish a lipid‐based diagnosis of breast cancer with higher accuracy, using a simpler approach. Rapid mass spectrometry for breast cancer

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 19 publications
(21 reference statements)
1
29
0
Order By: Relevance
“…Experiments have shown that a lipid is a useful biomarker for cancer diagnosis [ 63 , 64 ], especially in breast cancer. Therefore, the authors of this paper summarize the lipid molecules with diagnostic potential related to breast cancer in patients ( Table 1 ) [ 11 , 42 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 ].…”
Section: Role Of Lipid In the Diagnosis Of Breast Cancermentioning
confidence: 99%
“…Experiments have shown that a lipid is a useful biomarker for cancer diagnosis [ 63 , 64 ], especially in breast cancer. Therefore, the authors of this paper summarize the lipid molecules with diagnostic potential related to breast cancer in patients ( Table 1 ) [ 11 , 42 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 ].…”
Section: Role Of Lipid In the Diagnosis Of Breast Cancermentioning
confidence: 99%
“…This was in good agreement with previous reports demonstrating significant changes in lipid profiles in cancer patients [ 20 – 22 ]. Other reports have demonstrated the high discriminant accuracy of PESI-MS and machine learning for head and neck cancer and breast cancer (92.9 and 96.0%, respectively) [ 12 , 23 ]. Similarly, this system also could rapidly discriminate CRLM from non-cancerous tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The PESI‐MS analysis was performed using a triple quadrupole mass spectrometer (DPiMS‐8060; Shimadzu Corp.), which has a PESI ion source that replaces the ESI module of the original LCMS‐8060 spectrometer. The mass spectra were acquired for nonneoplastic and PDAC specimens in the positive ion mode, and all subsequent analyses were performed as previously described previously 5–9 …”
Section: Methodsmentioning
confidence: 99%